2022
DOI: 10.1088/1741-4326/ac652c
|View full text |Cite
|
Sign up to set email alerts
|

Study on the growth and redistribution of deuterium–deuterium layer driven by temperature gradient

Abstract: We report results of crystal growth, layering of the deuterium-deuterium (D2) layers in cylindrical cryogenic targets. For the first time, we realized the global coverage of the D2 layer on the inner surface of the capsule through the crystal growth of D2 ice, and the control of the temperature field without the infrared radiation, foam lining, and magnetic field. Analysis of the image of X-ray phase contrast imaging shows that the thickness of the D2 layer is about 36.53 μm, and the inner surface roughness is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The capsules are further cooled below the deuterium solidification temperature when the amounts of the liquid fuel inside the capsules meet the design requirements. Following specific procedures of temperature control [21,22], it is found that a uniform D-ice layer can survive for a few minutes inside the capsule. We repeated the procedures of D-ice layering fourteen times for a single target, and by characterizing the ice layer quality with phase contrast imaging (figure 2), we found that there was a 72% chance that the amplitude of mode 1 was less than 2.8 µm, and the RMS of the power spectrum in modes 2-100 was 2.2 µm in average.…”
Section: Methodsmentioning
confidence: 99%
“…The capsules are further cooled below the deuterium solidification temperature when the amounts of the liquid fuel inside the capsules meet the design requirements. Following specific procedures of temperature control [21,22], it is found that a uniform D-ice layer can survive for a few minutes inside the capsule. We repeated the procedures of D-ice layering fourteen times for a single target, and by characterizing the ice layer quality with phase contrast imaging (figure 2), we found that there was a 72% chance that the amplitude of mode 1 was less than 2.8 µm, and the RMS of the power spectrum in modes 2-100 was 2.2 µm in average.…”
Section: Methodsmentioning
confidence: 99%